2013
DOI: 10.1007/s13762-013-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, biochemical and clastogenic response of chlorpyrifos and carbendazim in milkfish Chanos chanos

Abstract: Carbendazim and Chlorpyrifos are some of the most widespread environmental contaminants of major concern to human and animal reproductive health. Acute toxicity test results for pesticides were evaluated by the Probit analysis method and 96 h LC 50 values for C. chanos exposed to chlorpyrifos was 3.73 and 11.5 lg l -1 for carbendazim. Chlorpyrifos and carbendazim significantly decreased total protein, catalase, glutathione S-transferase and acetyl choline esterase and induced lipid peroxidation. Maximum effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 42 publications
3
21
0
1
Order By: Relevance
“…The generation of ROS by environmental contaminants and subsequent oxidative damage may negatively affect tadpole reproduction and development and is related to amphibian population declines (Costa et al, 2008); therefore, there may be population-level consequences of these low-dose exposures. Carbendazim has previously been associated with lipid peroxidation in milk fish (Palanikumar et al, 2014) and in rats (Rajeswary et al, 2007), although only developmental and genotoxic effects have been measured thus far in amphibians (Yoon et al, 2008;ZollMoreux and Ferrier, 1999), despite the wide usage and detection of carbendazim in surface waters at low concentrations (Palma et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of ROS by environmental contaminants and subsequent oxidative damage may negatively affect tadpole reproduction and development and is related to amphibian population declines (Costa et al, 2008); therefore, there may be population-level consequences of these low-dose exposures. Carbendazim has previously been associated with lipid peroxidation in milk fish (Palanikumar et al, 2014) and in rats (Rajeswary et al, 2007), although only developmental and genotoxic effects have been measured thus far in amphibians (Yoon et al, 2008;ZollMoreux and Ferrier, 1999), despite the wide usage and detection of carbendazim in surface waters at low concentrations (Palma et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had also shown that carbendazim was harmful to Prussian carp embryonic development and hatching, and its application could seriously affect the macroinvertebrate community [8,9]. Since most published studies focused on the chronic toxicity of carbendazim to aquatic organisms [9,10], more consideration should be given to the potential hazards caused by carbendazim to reproduction and endocrine system in fish species, especially in the early life stages.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to these studies, in the present study, growth rate of the fish was significantly reduced by carbosulfan. Recent studies indicate that pesticides significantly decrease the total protein in the tissues (Palanikumar et al, 2014;Harabawy and Ibrahim, 2014). Total protein content in different tissues of fish decreased with increasing concentration of lambda-cyhalothrin and highest decline was observed in liver protein content when compared with : Differences between carbosulfan-exposed fish and control fish were significant (P< 0.05).…”
Section: Discussionmentioning
confidence: 91%